Theoretical considerations of romanticism - Aleksić Slađana V. (Zbornik Radova Filozofskog Fakulteta u Prištini, 2023)
The changes brought about by romanticism in the understanding of literature do not mean only the end of the classicist period. By destroying normativity as a form of relationship to creativity, the romantics emphasized the principle: as many writers as many sources of rules. Hence, the way was opened to the predominance of another poetics, descriptive, which has remained dominant even in our time. One of the most important results that romanticism brought in the study of literature is the orientation towards the study of concrete literary phenomena. This orientation brings to the fore the possibilities of studying concrete phenomena offered by the disciplines of literary criticism and literary history. The paper presents romantic poetic attitudes and theoretical considerations of romanticism.